Analysis of heel formation and influencing factors during the thermal regeneration process of saturated activated carbon - ZHANG Weiye; SHEN Jing; PAN Zihe; SONG Yipeng; CHENG Huaigang; ZHANG Huirong (Gongye shui chuli)
Thermal regeneration is the most commonly used method for treating saturated activated carbon due to its high processing capacity and non-selectivity for adsorbates. However, during thermal regeneration, the adsorbates go through decomposition, polymerization and other reactions inside the activated carbon. The heels are deposited in the pores, causing blockage and decreasing the specific surface area and pore volume of the activated carbon after thermal regeneration. To ensure successful thermal regeneration, it is crucial to understand the mechanism and key factors influencing heel deposition, reduce its occurrence, and maximize the restoration of adsorption performance. This article provided an overview of the thermal regeneration process of activated carbon, and the mechanisms of heel deposition during regeneration. It focused on the characteristics of heel deposition under single and mixed adsorbates in the regeneration process, as well as the relationship between the physicochemical properties of adsorbates, activated carbon and heel deposition. The influence of thermal regeneration temperature, atmosphere, regeneration heating rate, purge gas flow rate, and other operating conditions on heel deposition was elucidated. Accordingly, recommendations were provided for the future industrial development of activated carbon regeneration.